Spatial-Temporal Evolution Characteristics of Vegetation Coverage and Urbanization Expansion in Dongguan Based on Remote Sensing - Zhang, Qiuhui; Wang, Ruei-Yuan (International Journal of Environment, Agriculture and Biotechnology, 2023)
The purpose of this study is to use the Landsat satellite image of Dongguan from 2005 to 2021, combining the dimidiate pixel model and stochastic matrix method, to calculate the vegetation coverage grade and land use type area, express the urbanization process with construction land, and analyze the relationship between the temporal and spatial evolution characteristics of vegetation coverage and urbanization expansion. The results indicate that: (1) The overall distribution of vegetation coverage is consistent, showing a spatial distribution characteristic of "high in the east, low in the west, and lowest in the north". (2) During this period, the overall coverage area of medium low, medium, and medium high vegetation decreased, while both low and high vegetation coverage areas increased. (3) The area of construction land has increased significantly, with the increased built-up area coming from bare land, followed by vegetation and water bodies. (4) The spatio-temporal evolution characteristics of vegetation coverage are closely related to urbanization expansion. This study can provide reasonable scientific data support and an effective decision-making basis for evaluating the regional ecological environment, construction, and urban development of Dongguan City.